BISMUTH TELLURID WASTE PROCESSING - M. V. Tsygankova; E. A. Perminova; M. T. Chukmanova; O. A. Raikina (Тонкие химические технологии)
The main stages of bismuth telluride processing comprising sintering with NaOH, leaching and precipitation were investigated. Bi2Te3 samples produced by "ADV Engineering" were used as starting compounds. The studies revealed regularities of tellurium behavior during the sintering of Bi2Te3 with NaOH and the resulting the solid residue leaching. It was noted that annealing at 350-450°C with NaOH transforms tellurium into Na2TeO3, which is an appropriate form for further dissolution and separation from bismuth. Increasing temperature results in Na2TeO3 oxidation and formation of the water-insoluble compound Na2TeO4. Thus, it decreases tellurium extraction degree during the leaching. It has been shown that increasing temperature from 8 to 25°C at the step of tellurium hydrolytic precipitation slightly affects the extraction degree, the value of which is 93.5-98.2%.